2003
DOI: 10.1002/mus.10386
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber number in the biceps brachii muscle of young and old men

Abstract: We have compared the number of muscle fibers in the biceps brachii muscle (BB) of six old men (82.3 +/- 4.3 years) and six young men (21.2 +/- 1.9 years). Muscle fiber number was estimated by dividing the maximal area of the BB, determined with magnetic resonance imaging, by the mean fiber area of the BB determined in a muscle biopsy. The percentage of type II fibers in the BB ( approximately 60%) and the type I fiber area were not different between the groups. The BB area (-26%), type II fiber area (-24%), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(90 citation statements)
references
References 48 publications
2
80
1
1
Order By: Relevance
“…Whereas some studies found no significant difference (Aniansson et al, 1992(Aniansson et al, , 1986Coggan et al, 1992;Grimby, Danneskiold-Samsoe, Hvid, & Saltin, 1982;Klein, Marsh, Petrella, & Rice, 2003;Lexell, Henriksson-Larsen, Winblad, & Sjostrom, 1983), others showed a decrease in Type II fiber proportion (Aniansson et al, 1992;Fayet, Rouche, Hogrel, Tome, & Fardeau, 2001;Larsson et al, 1979;Larsson, Sjodin, & Karlsson, 1978;Lexell, Downham, & Sjostrom, 1986;Monemi, Eriksson, Eriksson, & Thornell, 1998;Poggi et al, 1987). This decrease seems to appear between the ages of 76 and 80 years, whereas there was no change of proportion between 69 and 76 years (Aniansson et al, 1992).…”
Section: Fiber-type Proportionmentioning
confidence: 96%
See 1 more Smart Citation
“…Whereas some studies found no significant difference (Aniansson et al, 1992(Aniansson et al, , 1986Coggan et al, 1992;Grimby, Danneskiold-Samsoe, Hvid, & Saltin, 1982;Klein, Marsh, Petrella, & Rice, 2003;Lexell, Henriksson-Larsen, Winblad, & Sjostrom, 1983), others showed a decrease in Type II fiber proportion (Aniansson et al, 1992;Fayet, Rouche, Hogrel, Tome, & Fardeau, 2001;Larsson et al, 1979;Larsson, Sjodin, & Karlsson, 1978;Lexell, Downham, & Sjostrom, 1986;Monemi, Eriksson, Eriksson, & Thornell, 1998;Poggi et al, 1987). This decrease seems to appear between the ages of 76 and 80 years, whereas there was no change of proportion between 69 and 76 years (Aniansson et al, 1992).…”
Section: Fiber-type Proportionmentioning
confidence: 96%
“…One study reported that this loss of fibers mainly affected Type II fibers (Lexell et al, 1983). One study investigating the biceps brachii, however, revealed no loss of fibers (Klein et al, 2003).…”
Section: Number Of Fibersmentioning
confidence: 99%
“…Most papers have reported that differences by gender are observed in diameter of muscle fibers. However, regarding the ratio of Type I and II fibers in quadriceps femoris, one report indicated that females display a higher ratio of Type I fibers 27) , another showed that males display a higher ratio of Type I fibers 30) , and a third report found no gender differences 3) . This may indicate that no clear differences by gender exist.…”
Section: Effect Of Gender On Mfcvmentioning
confidence: 98%
“…Mitochondrial density has been found to be lower in their skeletal muscle of older individuals, which could further diminish capacity for endurance work. Thus, it may be that aging-related atrophy of skeletal muscle plays some role in the aging-related decline in work endurance [34] and strength [58].…”
Section: Introductionmentioning
confidence: 99%